Effectiveness of Carbon Ion Radiation in Locally Advanced Pancreatic Cancer - Liermann, Jakob; Naumann, Patrick; Weykamp, Fabian; Hoegen, Philipp; Debus, Juergen; Herfarth, Klaus (Frontiers in Oncology, 2021)
Purpose: Effective treatment strategies for unresectable locally advanced pancreatic cancer (LAPC) patients are eagerly warranted. Recently, convincing oncological outcomes were demonstrated by carbon ion radiotherapy. Nevertheless, there is a lack of evidence for this modern radiation technique due to the limited number of carbon ion facilities worldwide. Here, we analyze feasibility and efficacy of carbon ion radiotherapy in the management of LAPC at our institution. Methods: Between 2015 and 2020, 21 LAPC patients were irradiated with carbon ions with a total dose of 48 Gy (RBE) in single doses of 4 Gy (RBE). Three patients (14%) were treated with concomitant chemotherapy with gemcitabine 300 mg/m2 body surface weekly. Toxicity rates were extracted from the charts. Overall survival, progression free survival, local control and locoregional control were evaluated using Kaplan-Meier estimates. Results: One patient developed ascites CTCAE grade III during radiotherapy, which was related to a later histologically confirmed metachronous peritoneal carcinomatosis. No further higher-graded toxicity could be observed. The most common symptoms were nausea and abdominal pain. After a median estimated follow-up time of 19.1 months, the median progression free survival was 3.7 months and the median overall survival was 11.9 months. The estimated 1-year local control and locoregional control rates were 89% and 84%, respectively. Conclusion: Carbon ion radiotherapy of LAPC patients is safely feasible. Local tumor control rates were high. Nevertheless, compared to historical data, an overall survival improvement could not be observed. This could be explained by the poor prognosis of the selected underlying patients that mostly did not respond to prior chemotherapy as well as the early and frequent emergence of distant metastases that demonstrate the necessity of additional chemotherapy in further studies.